Caminho de Cora Coralina em Goiás : significados, usos e relações sociais - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
This research aims to understand the relationship between tourism and the territory of the Longdistance trail (LDT) Caminho de Cora Coralina (CCC), with spatial cutout in the municipality of Goiás. With almost 300 km, the CCC interconnects the cities of Corumbá de Goiás to the city of Goiás. This research will use documentary research and bibliographic research as indirect documentation, as direct documentation, exploratory field research is used. The bicycle will be used as transportation in the fieldwork. Semi-structured interviews were conducted with subjects who somehow got involved with the trail. To understand this process through a geographical approach, the territory is used as a category of analysis. How does a trail used at the time of gold exploration and the expansion of the population of Brazil, become a tourism product? What is the relationship between tourism and territory influenced by the implementation of the CCC? The LDTs connect the landscape in order to promote ecological corridors, enabling the generation of jobs and income, especially for the municipalities present along the way. It seeks to understand how the CCC influences the territory where it is implemented. The potential for tourism and the generation of opportunities that the LDTs have been perceived, especially the CCC, on the other hand, the tourist activity causes impacts on the political, economic, cultural and natural aspects where it is implemented, and can be beneficial to residents if there is a tourism planning involving mainly local residents, businessmen and the public authorities of the various spheres. The results of the dissertation also show that the Longdistance trails are an option to diversify the tourist offer, in a decentralized way, starting in many cases from the community itself. At the CCC, the role of the government was essential for its planning and implementation, as well as the participation of residents, volunteers, businessmen and supporters of the trails.
Caminho de Cora Coralina in Goiás : meanings, uses and social relations
Keywords: Trilhas de longo curso; Cidade de Goiás; Território; Turismo; Caminho de Cora Coralina; Long-distance trails; City of Goiás; Territory; Tourism; CIENCIAS HUMANAS::GEOGRAFIA